2019
DOI: 10.3390/ani9090640
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mineral Composition in Commercial Extruded Dry Dog Food by Near-Infrared Reflectance Spectroscopy

Abstract: Simple SummaryMineral content in dog food is essential to ensure animals’ adequate development and health status, but its analysis is time-consuming and companies are not always equipped with the technology to perform it. Near-infrared spectroscopy (NIRS) is a rapid, objective, easy to manage, chemical-free, and non-destructive method that is already available in the food industry for the prediction of gross composition (e.g., moisture, protein, fat, etc.). However, this technological approach is not yet used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
(85 reference statements)
2
12
2
Order By: Relevance
“…Furthermore, for the manufacturing companies, it is important to monitor the mineral content of foods, for its impact on the animals’ health and growth [ 11 ]. Both macrominerals and trace minerals exert important functions in the maintenance of homeostasis [ 12 , 13 , 14 ], and their excess or deficiency can impair animals’ health [ 15 ]. Thus, the mineral content of dog food needs to be frequently monitored with an easy and fast method.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for the manufacturing companies, it is important to monitor the mineral content of foods, for its impact on the animals’ health and growth [ 11 ]. Both macrominerals and trace minerals exert important functions in the maintenance of homeostasis [ 12 , 13 , 14 ], and their excess or deficiency can impair animals’ health [ 15 ]. Thus, the mineral content of dog food needs to be frequently monitored with an easy and fast method.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to a recent work using a microplate colorimetric assay [ 13 ], the strategy proposed here is more straightforward as it does not require the inclusion of ion masking reagents or the application of partitioning correction calculations. Compared to the fast method proposed by Goi et al [ 14 ], our approach provides the value of the total Zn as a digestion process is performed before the fluorimetric reaction while the near-infrared reflectance spectroscopy-based method can only detect Zn associated with organic complexes, providing underestimated results for dog food supplemented with inorganic forms of Zn. Finally, compared to other approaches that applied AAS [ 26 ] or ICP-MS [ 7 ], the method proposed here allows the simultaneous determination of up to 96 samples, without requiring expensive equipment or application of the standard addition method.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, these methods require trained personnel and high-cost/high maintenance equipment. Thus, there are some rapid and low-cost methods for zinc determination, based on fluorimetric [ 11 ] or colorimetric assays [ 12 , 13 ] and on near-infrared reflectance spectroscopy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In pet food, it is common practice to supplement diets with a Zn level above the minimum requirement to prevent symptoms of deficiency [12]. Goi et al [68] found that in the tested extruded commercial dog foods the amounts of Zn were greater than the established safe limit, and the average content of all foods was close to the recommended maximum (mean 19.02 g/100 g DM). In turn, a mean above the MLL of Zn in twenty dry complete dog foods for adult dogs and six foods for puppies (mean 32.5 and 27.6 g/100 g DM, respectively) was found in a study conducted by Pereira et al [11].…”
Section: Trace Elementsmentioning
confidence: 96%